Pengaruh Self Confidence Terhadap Kemampuan Komunikasi Matematis Siswa Madrasah Ibtidaiyah Pada Materi Bangun Ruang - Maulani, Leni; Permana, Dian (Moderasi : Journal of Islamic Studies, 2023)
This study aims to examine the influence of self-confidence on the mathematical communication ability of fifth-grade students at Madrasah Ibtidaiyah in the topic of three-dimensional geometry. A quantitative approach with a non-experimental correlational design was employed. The sample consisted of 28 students from a Madrasah Ibtidaiyah in Garut Regency, West Java, Indonesia. The instruments used in this study included a self-confidence questionnaire and a written test to assess students' mathematical communication skills. Data analysis using simple linear regression revealed a significant effect of self-confidence on students' mathematical communication ability, with a significance value of 0.002 (p < 0.05). The coefficient of determination (R²) was 0.314, indicating that self-confidence contributes 31.4% to students’ mathematical communication performance. These findings suggest that students with higher self-confidence tend to demonstrate better mathematical communication skills. The study recommends that teachers and schools give greater attention to fostering students’ self-confidence as a means to support success in mathematics learning